Reframing Devotion in the Later Cinquecento: The Madonna di Mongiovino and Catholic Reform - Caldwell, Dorigen (The sixteenth century journal, 2024)
The proliferation of miracle-working images in Italy from the end of the fifteenth century on has been well documented, as has the concomitant emergence of the sanctuary church. Less attention, however, has been given to the fortune of these sites in the later sixteenth century, when the zeal they incited in local populations was viewed by Catholic Church authorities as a powerful tool for engaging the faithful at a pivotal time of Catholic renewal - if harnessed correctly. According to visitation reports, superstitious practices were not uncommon, and greater scrutiny was afforded to both new prodigies and established cults; but the Catholic Church hierarchy continued to defend the veneration of miraculous images, and the latter years of the cinquecento saw the renovation of a number of key image shrines, including the focus of the current study. Situated in western Umbria, the Santuario di Mongiovino was the subject of an extensive decorative campaign during the 1560s to 1580s, and involved artists, such as Niccolò Circignani, who would also work on papal projects in Rome. Drawing on a range of textual sources, as well as a close analysis of the decorative reframing of the cultic image, I argue that the iconographic program employed at the site should be viewed in relation to contemporary debates around the use of religious imagery in churches. In particular I posit that the concerns voiced in the written record at the time, whether in treatises or visitation reports, may also have informed the way in which miraculous images were presented to the faithful, resulting in solutions that helped to underline the Catholic Church's position on the cult of saints, the role of images in devotion, and the primacy of Christ in the bestowing of grace.